Isolation, identification and probiotic characteristics of lactic acid bacteria from traditional koumiss in Xinjiang - GUO Lidong, MAOMULIDAN·Mijiti, WANG Liqun, LU Xi, WANG Shuotong, ZHANG Shen (Zhongguo niangzao, 2025)
To enrich probiotic lactic acid bacteria resources, the strains of lactic acid bacteria were isolated through traditional culture isolation method from the traditional naturally fermented koumiss in Xinjiang, identified through morphological observation and molecular biology techniques, and their probiotic characteristics, including the acid and bile tolerance, hydrophobicity, antibacterial ability, antioxidant activity, stress resistance, carbohydrate utilization and antibiotic sensitivity, were evaluated. The results showed that a total of 9 strains of lactic acid bacteria were isolated, 3 strains (K-1、K-5、K-6) were identified as Levilactobacillus brevis, and 6 strains (K-2、K-3、K-4、K-7、K-8、K-9) were identified as Lactiplantibacills plantarum. Among them, the counts of viable bacteria of strains K-1, K-2 and K-3 remained unchanged for 2 h under the condition of pH 2.0, and the strain K-2 could completely tolerate 0.3% bile for 4 h. The hydrophobicities of the strain K-7 to the xylene, hexadecane and chloroform were the highest, reaching over 80%. Most strains could inhibit the growth of Escherichia coli, Salmonella paratyphi and Staphylococcus aureus. The scavenging abilities of the cell-free supernatants of all strains to hydroxyl radical and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical were significantly higher than 1.5 mg/ml vitamin C (P<0.05). The strains K-3 and K-8 could completely tolerate 4% NaCl, and the strain K-2 had the optimal tolerance to ethanol. It was species-specific and strains-specific for the carbohydrate utilization and antibiotic sensitivity of all lactic acid bacteria isolates. In conclusion, all the isolates of lactic acid bacteria had superior in vitro probiotic properties.